Pengembangan Game Edukasi Pengenalan Rambu-Rambu Lalu Lintas TK Kemala Bhayangkari 31 Salatiga (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Educational game is a game which is specifically designed as a tool to accomplish educational needs. Therefore, it has to be projected in an exact precision to achieve its goal: educating, and increasing the user knowledge and skills. There are some problems which frequently happened at TK Kemala Bhayangkari 31 Salatiga, firstly, the number of props of traffic signs is limited so it is not proportional to the number of meetings in the existing curriculum and students must repeat the same material. Secondly, there isn’t suitable learning support media to add props to traffic signs that are still lacking.The software used in this game development was Adobe Flash CS6. The research was conducted through R&D; Research and Development method by processed through some stages. First, problem identification stage, then, data collection, product design, design validation, design revision, and the final step was the product trials. The validation was carried out by the expert validators and product user.Based on the research conducted, it concluded that this game has 43 signs which fulfill the number of signs that must be taught to students according to the curriculum at TK Kemala Bhayangkari 31 Salatiga, 18% which is most often found on the road from the total number of traffic signs in the Minister of Transportation Regulation No. 13 years 2014.